1996
DOI: 10.1177/172460089601100405
|View full text |Cite
|
Sign up to set email alerts
|

Are Diabetic Metabolic Compensation and CA19.9 Really Correlated?

Abstract: Diabetes has been claimed to be a risk factor for pancreatic carcinoma, but it is probably a consequence of gland invasion from the neoplastic tissue. A link between diabetes and pancreatic carcinoma was suggested by means of biochemical markers of the diseases, namely glycated hemoglobin and CA19.9. Moreover, CA19.9 was proposed as a sensitive and useful marker of the severity of exocrine damage in diabetes, since the mucin decreased when metabolic compensation improved. We examined 64 diabetic patients (36 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…In contrast to Benhamou et al, 64 diabetic patients examined by Banfi et al [16] showed no correlation between CA 19-9 and biochemical markers of metabolic compensation in diabetes. In our study we also found that CA 19-9 levels were higher in diabetic patients in comparison to controls (P < 0.001 ).…”
Section: Discussioncontrasting
confidence: 41%
“…In contrast to Benhamou et al, 64 diabetic patients examined by Banfi et al [16] showed no correlation between CA 19-9 and biochemical markers of metabolic compensation in diabetes. In our study we also found that CA 19-9 levels were higher in diabetic patients in comparison to controls (P < 0.001 ).…”
Section: Discussioncontrasting
confidence: 41%
“…The mean level of serum CA19-9 in diabetic patients was 32.8 ± 25.8 or 46.0 ± 22.4 (U/ml) (Nakamura et al 1986;UygurBayramicli et al 2007), far less than pancreatic cancer patients according to the literature (Chang et al 2007;Guo et al 2009;Kang et al 2007). Paradoxically, no correlation between CA 19-9 and biochemical markers of metabolic compensation in diabetes was reported by Banfi et al (1996). The mechanism for an elevation of serum CA 19-9 in patients with diabetes mellitus may be the increase in sialic acid levels and the accelerated sialylation of carbohydrate chains (Shimojo et al 1990).…”
Section: Discussionmentioning
confidence: 91%
“…Bayramicli et al found significantly higher CA19-9 levels in type 2 diabetic patients than controls, however they did not investigate the relation between CA19-9 and glycemic control [7]. Benhamou et al [8] found a significant correlation between HbA1c, fasting blood glucose and CA19-9, on the other hand Banfi et al [9] did not observe such a correlation. Gul et al , also found higher CA 19-9 levels in diabetic patients than controls [10].…”
Section: Introductionmentioning
confidence: 99%